A local obstacle avoidance control law for mobile robot navigation based on Beam Curvature Method - Cherni, Faten; Boutereaa, Yassine; Rekik, Chokri; Derbel, Nabil (2015 IEEE 12th International Multi-Conference on Systems, Signals & Devices (SSD15), 2015)
This paper focuses on the based Beam Curvature Method for two wheeled mobile robot navigation in partially known environments. Local obstacle avoidance problem by indoor mobile robots has been a well-researched subject by several robotics researchers. There are various reactive strategies which operate in the velocity space such as the Dynamic Windows Approach (DWA), the Curvature Velocity Method (CVM), the Lane Curvature Method (LCM) and the Beam Curvature Method (BCM). These approaches formulate the local obstacle avoidance problem and take into account the robot dynamics and environment physical constraints. In this paper we present a comparison between two methods based on the Beam Curvature Method and the Dynamic Window Approach.